Transformasi Sosial Pribumi Depok Tahun 1930-1960 - Suryana, Asep (P2KK LIPI, 2004)
The article deals with the social transformation of the indigenous people of Depok from 1930 until 1960. Substancially, the social transformation had made public sphere of the indigenous people of Depok wider, and it produced their new structure of socioeconomic significantly. In this context, they were so selective in their adaptation processes. Actually, the patterns of their adaptation had rational calculation itself that based on subsistence principles.